Soul Restoration in Islamic Tradition (Ibn Tufail's Perspective of Tazkiyya an-Nafs Model) - Jarman Arroisi; Erva Dewi Arqomi Puspita (Jurnal Ushuluddin, 2020)
The modern era has had both positive and negative impacts on the progress of human civilization. The positive impact can be seen from the increasing advances in technology and science that help human life. Meanwhile, one of the negative impacts that emerged from the modern era is the spread of mental health problems in society. Not a few in modern society there are several symptoms and mental health problems that make it difficult for someone to find happiness. This article aims to explain efforts to cleanse the soul in Islamic tradition such as the pattern of cleansing the soul by Ibn Tufail. By using a descriptive critical analysis method with this type of literature research, this research found several important points. First, tazkiyya al-nafs is an important effort that must be made by someone to get a sense of happiness. Second, one of the important strategies and ways to get happiness according to Ibn Tufail is to attain knowledge of God. Third, if someone has come to the knowledge of God, then he will come to Ma'rifatullah. The attainment of this ma'rifatullah stage can only be achieved by someone if that person has cleansed his soul. With tazkiyya al-nafs that is done consistently one will come to what is called musyahadatullah or ma'rifah billah.